Characterization of a potent and highly unusual minimally-enhancing antibody directed against dengue virus - Renner, Max (Nat Immunol, 2018)
Dengue virus is a major pathogen and severe infections can lead to life threatening dengue hemorrhagic fever (DHF). Dengue exists as four serotypes and DHF is often associated with secondary heterologous infections. Antibody dependent enhancement (ADE) may drive higher virus loads in these secondary infections, and is purported to result from antibodies that recognize dengue but fail to fully neutralize. We have characterized two antibodies, 2C8 and 3H5, which bind to the envelope protein. 3H5 is highly unusual as it is both potently neutralizing, but promotes little if any ADE, whereas 2C8 has strong capacity to promote ADE. We show that 3H5 shows resilient binding in endosomal pH conditions and neutralizes at low occupancy. Immune complexes of 3H5 and dengue virus do not efficiently interact with Fcγ receptors, which we propose is due to the binding mode of 3H5 and which constitutes the primary mechanism of how ADE is avoided.